Crystalline polymorphs and their uses as thyroid hormone receptor agonists - Patents.com

JP2025505211APending Publication Date: 2025-02-21シーツァン ハイスコ ファーマスーティカル カンパニー リミテッド
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024547012
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-01-04
Filing Date
2023-02-07
Publication Date
2025-02-21

AI Technical Summary

Benefits of technology

【0113】 本発明は、以下の有益な効果を有する。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025505211000001_ABST
    Figure 2025505211000001_ABST
Patent Text Reader

Abstract

The present invention discloses a crystalline polymorph of the compound of formula I, (R)-2-(3,5-dichloro-4-((7-(methyl-d3)-1-oxo-2,5,6,7-tetrahydro-1H-cyclopenta[d]pyridazin-4-yl)oxy)phenyl)-3,5-dioxo-2,3,4,5-tetrahydro-1,2,4-triazine-6-carbonitrile, and its preparation method, pharmaceutical composition and application in medicine. [Formula 1] TIFF2025505211000048.tif46160
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the pharmaceutical field, specifically to crystalline polymorphs of thyroid hormone receptor agonists, and their preparation and use. [Background technology]

[0002] Classical familial hypercholesterolemia (FH) is an autosomal (co)dominant genetic disease, the main clinical symptoms of which are obvious elevation of serum low density lipoprotein cholesterol (LDL-C) levels and skin / tendon xanthomas, which may lead to premature cardiovascular disease. Common FH is divided into heterozygous familial hypercholesterolemia (HeFH) and the rarer homozygous familial hypercholesterolemia (HoFH). Statistics show that the prevalence of HeFH is as high as 0.2%-0.48%. FH is generally caused by an inactive mutation of the LDL receptor (LDLR). In clinical medication, statins are the first choice for treatment, which can not only reduce LDL-C levels but also improve the prognosis of FH patients. For patients with poor therapeutic effects or side effects of statins, they can be treated in combination with the cholesterol absorption inhibitor ezetimibe. For patients who have not yet reached the goal of the above treatment, PCSK9 inhibitors can be additionally administered. Although there are corresponding treatment modalities for HeFH, many patients (up to 40% of HeFH patients) still cannot reach the cholesterol (LDL-C) target after receiving these treatments, and the accumulation of cholesterol in their bodies becomes a lifelong burden.

[0003] Thyroid hormone receptors are divided into two subtypes, α and β. After binding to the β subtype receptor, thyroid hormone can promote cholesterol metabolism. Therefore, in recent years, many thyroid hormone analogs or thyroxine mimetics that selectively stimulate the β subtype have been developed. Clinical results of the oral agonist MGL-3196 developed by Madrigal have shown that it can significantly reduce the level of LDL-C in patients and improve metabolic syndrome (e.g., insulin resistance and dyslipidemia) and fatty liver disease (including lipid toxicity and inflammation).

[0004] WO2019240938A1 describes the compound (R)-2-(3,5-dichloro-4-((7-(methyl-d3)-1-oxo-2,5,6,7-tetrahydro-1H-cyclopenta[d]pyridazin-4-yl)oxy)phenyl)-3,5-dioxo-2,3,4,5-tetrahydro-1,2,4-triazine-6-carbonitrile, which belongs to the thyroxine beta receptor agonists and is intended to be used for the treatment of primary hypercholesterolemia, and a preparation method is also disclosed. However, it is an urgent problem to develop a drug crystal form of the compound that is more suitable for drug formation, especially a crystal form with improved stability, hygroscopicity, storage stability and / or efficacy, to obtain good effects in pharmaceuticals. Summary of the Invention [Means for solving the problem]

[0005] The present invention provides a crystalline polymorph of the compound of formula I, which has excellent properties such as high purity, good solubility, stable physical and chemical properties, resistance to high temperature, high humidity and strong light exposure, and low hygroscopicity.

[0006] A crystalline polymorph of the compound of formula I, [ka] Here, n is 0 to 2, and X is H2O, 4-methyl-2-pentanone, toluene, DMF, acetone, ethyl acetate, DMSO, isopropyl acetate, dioxane, acetonitrile, tetrahydrofuran, or ethylene glycol monomethyl ether.

[0007] In some embodiments, n is 0 to 2. In some embodiments, n is 0 to 1.

[0008] In some embodiments, X is HO.

[0009] In some embodiments, n is 2, X is HO, and the crystalline polymorph is crystalline form A, and its X-ray powder diffraction pattern employing Cu-Kα radiation has characteristic diffraction peaks at the following 2θ positions: 5.68°±0.2°, 11.44°±0.2°, 17.19°±0.2°, 24.94°±0.2°, 26.40°±0.2°, and 29.47°±0.2°.

[0010] Furthermore, the X-ray powder diffraction pattern of said crystalline form A further has characteristic diffraction peaks at 2θ positions of 12.68°±0.2°, 19.44°±0.2°, 19.79°±0.2°, and 23.27°±0.2°.

[0011] Furthermore, the X-ray powder diffraction pattern of the crystalline form A has characteristic diffraction peaks at the following 2θ positions:

[0012] [Table 1]

[0013] Furthermore, for the crystalline form A, the X-ray powder diffraction pattern is essentially as shown in FIG.

[0014] Furthermore, said crystalline form A has a DSC diagram and / or a TGA diagram in FIG.

[0015] In some embodiments, n is 0.4, X is 4-methyl-2-pentanone, and the crystalline polymorph is crystalline form B, and its X-ray powder diffraction pattern employing Cu-Kα radiation has characteristic diffraction peaks at the following 2θ positions: 8.03°±0.2°, 11.05°±0.2°, 11.82±0.2°, 16.14±0.2°, 16.55°±0.2°, 22.01°±0.2°, 22.34°±0.2°, 23.43±0.2°, 24.34±0.2°, 25.18°±0.2°, and 29.30°±0.2°.

[0016] Furthermore, the X-ray powder diffraction pattern of the crystalline form B has characteristic diffraction peaks at the following 2θ positions:

[0017] [Table 2]

[0018] Furthermore, for the crystalline form B, the X-ray powder diffraction pattern is essentially as shown in FIG.

[0019] Furthermore, said crystalline form B has a DSC diagram and / or a TGA diagram in FIG.

[0020] In some embodiments, n is 0 and the crystalline polymorph is crystalline form C, and its X-ray powder diffraction pattern employing Cu-Kα radiation has characteristic diffraction peaks at the following 2θ positions: 11.03°±0.2°, 15.79°±0.2°, 16.97°±0.2°, 23.27°±0.2°, 23.76°±0.2°, and 27.61°±0.2°.

[0021] Furthermore, for said crystalline form C, its X-ray powder diffraction pattern further has characteristic diffraction peaks at the 2θ positions of 14.12°±0.2°, 19.73°±0.2°, 22.51°±0.2°, 25.37°±0.2°, 28.21°±0.2° and 33.73°±0.2°.

[0022] Furthermore, for said crystalline form C, its X-ray powder diffraction pattern has characteristic diffraction peaks at the following 2θ positions:

[0023] [Table 3]

[0024] Furthermore, for the crystalline form C, the X-ray powder diffraction pattern is essentially as shown in FIG.

[0025] Furthermore, said crystalline form C has a DSC diagram and / or a TGA diagram in FIG.

[0026] In some embodiments, n is 0.4, X is toluene, and the crystalline polymorph is crystalline form D, and its X-ray powder diffraction pattern employing Cu-Kα radiation has characteristic diffraction peaks at the following 2θ positions: 5.93±0.2°, 11.90°±0.2°, 13.38°±0.2°, 15.50°±0.2°, 16.84°±0.2°, 17.91°±0.2°, 18.51°±0.2°, 20.24°±0.2°, 20.86°±0.2°, 23.95°±0.2°, 26.25°±0.2°, 29.94°±0.2°, 32.48°±0.2°, and 36.29°±0.2°.

[0027] Furthermore, for said crystalline form D, its X-ray powder diffraction pattern is essentially as shown in FIG.

[0028] Furthermore, said crystalline form D has a DSC diagram and / or a TGA diagram in FIG.

[0029] In some embodiments, n is 0.8, X is DMF, and the crystalline polymorph is crystalline form E, and its X-ray powder diffraction pattern employing Cu-Kα radiation has characteristic diffraction peaks at the following 2θ positions: 4.75°±0.2°, 5.76°±0.2°, 8.23°±0.2°, 9.47°±0.2°, 10.83°±0.2°, 14.21°±0.2°, 16.43°±0.2°, 18.43°±0.2°, 18.70°±0.2°, 19.02°±0.2°, 22.84°±0.2°, and 26.42°±0.2°.

[0030] Furthermore, for the crystalline form E, the X-ray powder diffraction pattern is essentially as shown in FIG.

[0031] Furthermore, said crystalline form E has a DSC diagram and / or a TGA diagram in FIG.

[0032] In some embodiments, n is 1, X is acetone, and the crystalline polymorph is crystalline form F, and the X-ray powder diffraction pattern employing Cu-Kα radiation is 6.67°±0.2°, 7.65°±0.2°, 8.34°±0.2°, 10.17°±0.2°, 12.37±0.2°, 13.42°±0.2°, 15.48°±0.2°. The sample has characteristic diffraction peaks at the following 2θ positions: 18.49±0.2°, 19.05°±0.2°, 20.47°±0.2°, 21.64°±0.2°, 22.86°±0.2°, 23.17°±0.2°, 23.41°±0.2°, 24.88°±0.2°, 28.15°±0.2°, 28.75°±0.2°, and 32.85°±0.2°.

[0033] Furthermore, for the crystalline form F, the X-ray powder diffraction pattern is essentially as shown in FIG.

[0034] Furthermore, said crystalline form F has a DSC diagram and / or a TGA diagram in FIG.

[0035] In some embodiments, n is 1, X is ethyl acetate, and the crystalline polymorph is crystalline form G, and the X-ray powder diffraction pattern employing Cu-Kα radiation is 8.69°±0.2°, 9.14°±0.2°, 11.03°±0.2°, 11.88°±0.2°, 12.62°±0.2°, 13.53°±0.2°, 16.14°±0.2°, 16.66°±0.2°, 16.94°±0.2°, 17. It has characteristic diffraction peaks at the 2θ positions of 40°±0.2°, 18.70°±0.2°, 18.82°±0.2°, 19.19°±0.2°, 20.73°±0.2°, 22.82°±0.2°, 23.76°±0.2°, 24.15°±0.2°, 24.36°±0.2°, 24.79°±0.2°, 25.60°±0.2°, 26.28°±0.2°, 27.16°±0.2°, and 29.41°±0.2°.

[0036] Furthermore, for the crystalline form G, the X-ray powder diffraction pattern is essentially as shown in FIG.

[0037] Furthermore, said crystalline form G has a DSC diagram and / or a TGA diagram in FIG.

[0038] In some embodiments, n is 1, X is DMSO, and the crystalline polymorph is crystalline form H and its X-ray powder diffraction pattern employing Cu-Kα radiation has characteristic diffraction peaks at the following 2θ positions: 5.53°±0.2°, 8.54°±0.2°, 11.05°±0.2°, 16.59°±0.2°, 18.16°±0.2°, 21.04°±0.2°, 21.91°±0.2°, 22.16°±0.2°, 22.75°±0.2°, 23.45°±0.2°, 25.70°±0.2°, 26.65°±0.2°, and 27.57°±0.2°.

[0039] Furthermore, for the crystalline form H, the X-ray powder diffraction pattern is essentially as shown in FIG.

[0040] Furthermore, said crystalline form H has a DSC diagram and / or a TGA diagram in FIG.

[0041] In some embodiments, n is 0.9, X is isopropyl acetate, and the crystalline polymorph is crystalline form I, and the X-ray powder diffraction pattern employing Cu-Kα radiation is 8.36°±0.2°, 10.17°±0.2°, 11.36°±0.2°, 12.72°±0.2°, 13.20°±0.2°, 16.55°±0.2°. It has characteristic diffraction peaks at the 2θ positions of 16.78°±0.2°, 17.13°±0.2°, 18.92°±0.2°, 19.85°±0.2°, 23.50°±0.2°, 23.97°±0.2°, 24.50°±0.2°, 25.60°±0.2°, 26.79°±0.2°, and 30.00°±0.2°.

[0042] Furthermore, for the crystalline form I, the X-ray powder diffraction pattern is essentially as shown in FIG.

[0043] Furthermore, said crystalline form I has a DSC diagram and / or a TGA diagram in FIG.

[0044] In some embodiments, X is acetonitrile and the crystalline polymorph is crystalline form J, and the X-ray powder diffraction pattern employing Cu-Kα radiation is 10.07°±0.2°, 11.07°±0.2°, 11.53°±0.2°, 13.34°±0.2°, 14.08°±0.2°, 14.23°±0.2°, 14.51°±0.2°, 14.99°±0.2°, 15.17°±0.2°, 15.56°±0.2°, 15.83°±0.2°, 16.02°±0.2°, 16.70°±0.2° , 16.99°±0.2°, 17.75°±0.2°, 17.97°±0.2°, 18.35°±0.2°, 19.00°±0.2°, 20.10°±0.2°, 21.97°±0.2°, 22.47°±0.2°, 23.27°±0.2°, 24.11°±0.2°, 24.75°±0.2°, 25.60°±0.2°, 26.32°±0.2°, 27.29°±0.2°, 27.74°±0.2°, 28.66°±0.2°, and 29.45°±0.2°.

[0045] Furthermore, for the crystalline form J, the X-ray powder diffraction pattern is essentially as shown in FIG.

[0046] Further, the crystalline form J has a DSC diagram and / or a TGA diagram in FIG.

[0047] In some embodiments, n is 0.9, X is dioxane, and the crystalline polymorph is crystalline form K, and its X-ray powder diffraction pattern employing Cu-Kα radiation has characteristic diffraction peaks at the following 2θ positions: 7.63°±0.2°, 8.34°±0.2°, 22.26°±0.2°, 23.04°±0.2°, and 23.27°±0.2°.

[0048] Furthermore, for the crystalline form K, the X-ray powder diffraction pattern is essentially as shown in FIG.

[0049] Further, the crystalline form K has a DSC diagram and / or a TGA diagram in FIG.

[0050] In some embodiments, n is 2, X is HO, and the crystalline polymorph is crystalline form L, and its X-ray powder diffraction pattern employing Cu-Kα radiation has characteristic diffraction peaks at the following 2θ positions: 5.72°±0.2°, 11.49°±0.2°, 12.56°±0.2°, 14.33°±0.2°, 17.32°±0.2°, 25.33°±0.2°, and 26.25°±0.2°.

[0051] Furthermore, the X-ray powder diffraction pattern of the crystalline form L has characteristic diffraction peaks at the following 2θ positions:

[0052] [Table 4]

[0053] Furthermore, for the crystalline form L, the X-ray powder diffraction pattern is essentially as shown in FIG.

[0054] Furthermore, said crystalline form L has a DSC diagram and / or a TGA diagram in FIG.

[0055] In some embodiments, the crystalline polymorph is crystalline form M, and its X-ray powder diffraction pattern employing Cu-Kα radiation has characteristic diffraction peaks at the following 2θ positions: 4.73°±0.2°, 5.24°±0.2°, 6.56°±0.2°, 7.53°±0.2°, 8.31°±0.2°, 18.84°±0.2°, 21.48°±0.2°, and 22.88°±0.2°.

[0056] Furthermore, for the crystalline form M, the X-ray powder diffraction pattern is essentially as shown in FIG.

[0057] Furthermore, the crystalline form M has a DSC diagram and / or a TGA diagram in FIG.

[0058] In some embodiments, n is 0.6, X is acetonitrile, and the crystalline polymorph is crystalline form N, and its X-ray powder diffraction pattern employing Cu-Kα radiation has characteristic diffraction peaks at the following 2θ positions: 8.42°±0.2°, 9.08°±0.2°, 10.85°±0.2°, 16.86°±0.2°, and 17.23°±0.2°.

[0059] Furthermore, the X-ray powder diffraction pattern of the crystalline form N has characteristic diffraction peaks at the following 2θ positions:

[0060] [Table 5]

[0061] Furthermore, for the crystalline form N, the X-ray powder diffraction pattern is essentially as shown in FIG.

[0062] Further, the crystalline form N has a DSC diagram and / or a TGA diagram in FIG.

[0063] In some embodiments, n is 0.8, X is DMF, and the crystalline polymorph is crystalline form O, and its X-ray powder diffraction pattern employing Cu-Kα radiation has characteristic diffraction peaks at the following 2θ positions: 5.49°±0.2°, 8.64°±0.2°, 10.89°±0.2°, 11.45°±0.2°, 16.37°±0.2°, 18.55°±0.2°, 21.44°±0.2°, 22.14°±0.2°, 22.73°±0.2°, 22.98°±0.2°, 23.25°±0.2°, and 26.17°±0.2°.

[0064] Furthermore, for the crystalline form O, the X-ray powder diffraction pattern is essentially as shown in FIG.

[0065] Furthermore, said crystalline form O has a DSC diagram and / or a TGA diagram in FIG.

[0066] In some embodiments, n is 2, X is HO, and the crystalline polymorph is crystalline form P, and its X-ray powder diffraction pattern employing Cu-Kα radiation has characteristic diffraction peaks at the following 2θ positions: 5.76°±0.2°, 11.55°±0.2°, 17.38°±0.2°, 23.12°±0.2°, 24.50°±0.2°, and 26.58°±0.2°.

[0067] Furthermore, for said crystalline form P, its X-ray powder diffraction pattern further has characteristic diffraction peaks at the 2θ positions of 14.60°±0.2°, 17.13°±0.2°, 25.90°±0.2°, and 29.48°±0.2°.

[0068] Furthermore, the X-ray powder diffraction pattern of the crystalline form P has characteristic diffraction peaks at the following 2θ positions:

[0069] [Table 6]

[0070] Furthermore, for the crystalline form P, the X-ray powder diffraction pattern is essentially as shown in FIG.

[0071] Further, the crystalline form P has a DSC diagram and / or a TGA diagram in FIG.

[0072] In some embodiments, X is water and tetrahydrofuran, and the crystalline polymorph is crystalline form Q, and its X-ray powder diffraction pattern employing Cu-Kα radiation has characteristic diffraction peaks at the following 2θ positions: 7.55°±0.2°, 8.25°±0.2°, 10.09°±0.2°, 12.29°±0.2°, 15.42°±0.2°, 18.47°±0.2°, 18.96°±0.2°, 22.16°±0.2°, 22.90°±0.2°, 23.17°±0.2°, 23.54°±0.2°, 24.07°±0.2°, 24.79°±0.2°, and 25.97°±0.2°.

[0073] Furthermore, for the crystalline form Q, the X-ray powder diffraction pattern is essentially as shown in FIG.

[0074] Further, the crystalline form Q has a DSC diagram and / or a TGA diagram in FIG.

[0075] In some embodiments, n is 0.9, X is dioxane, and the crystalline polymorph is crystalline form R, and its X-ray powder diffraction pattern employing Cu-Kα radiation has characteristic diffraction peaks at the following 2θ positions: 7.53°±0.2°, 8.25°±0.2°, 10.07°±0.2°, 13.32°±0.2°, 15.32°±0.2°, 18.33°±0.2°, 22.14°±0.2°, 22.82°±0.2°, and 23.14°±0.2°.

[0076] Furthermore, for the crystalline form R, the X-ray powder diffraction pattern is essentially as shown in FIG.

[0077] Furthermore, the crystalline form R has a DSC diagram and / or a TGA diagram in FIG.

[0078] In some embodiments, n is 1, X is DMSO, and the crystalline polymorph is crystalline form S, and its X-ray powder diffraction pattern employing Cu-Kα radiation has characteristic diffraction peaks at the following 2θ positions: 7.74°±0.2°, 8.46°±0.2°, 10.29°±0.2°, 12.37°±0.2°, 13.55°±0.2°, 15.61°±0.2°, 18.65°±0.2°, 19.09°±0.2°, 23.23°±0.2°, 23.49°±0.2°, and 24.79°±0.2°.

[0079] Furthermore, for the crystalline form S, the X-ray powder diffraction pattern is essentially as shown in FIG.

[0080] Further, the crystalline form S has a DSC diagram and / or a TGA diagram in FIG.

[0081] In some embodiments, n is 1 and X is 4-methyl-2-pentanone, and the crystalline polymorph is crystalline form T, and its X-ray powder diffraction pattern employing Cu-Kα radiation has characteristic diffraction peaks at the following 2θ positions: 6.81°±0.2°, 6.98°±0.2°, 7.78°±0.2°, 9.76°±0.2°, 11.82°±0.2°, 13.65°±0.2°, 15.36°±0.2°, 17.42°±0.2°, 18.26°±0.2°, 18.51°±0.2°, 21.78°±0.2°, 22.22°±0.2°, 23.82°±0.2°, 25.04°±0.2°, and 28.52°±0.2°.

[0082] Furthermore, for the crystalline form T, the X-ray powder diffraction pattern is essentially as shown in FIG.

[0083] Furthermore, said crystalline form T has a DSC diagram and / or a TGA diagram in FIG.

[0084] In some embodiments, n is 1, X is acetonitrile, and the crystalline polymorph is crystalline form U, and its X-ray powder diffraction pattern employing Cu-Kα radiation has characteristic diffraction peaks at the following 2θ positions: 7.72°±0.2°, 8.42°±0.2°, 18.63°±0.2°, 23.25°±0.2°, and 23.49°±0.2°.

[0085] Furthermore, for the crystalline form U, the X-ray powder diffraction pattern is essentially as shown in FIG.

[0086] Further, the crystalline form U has a DSC diagram and / or a TGA diagram in FIG.

[0087] In some embodiments, n is 0 and the crystalline polymorph is crystalline form V, and its X-ray powder diffraction pattern employing Cu-Kα radiation has characteristic diffraction peaks at the following 2θ positions: 7.41°±0.2°, 11.05°±0.2°, 15.81°±0.2°, 16.97°±0.2°, 22.53°±0.2°, 23.29°±0.2°, and 27.63°±0.2°.

[0088] Furthermore, for said crystalline form V, its X-ray powder diffraction pattern further has characteristic diffraction peaks at the 2θ positions of 14.16°±0.2°, 15.59°±0.2°, 19.73°±0.2°, 21.33°±0.2°, 23.78°±0.2°, 25.39°±0.2° and 33.75°±0.2°.

[0089] Furthermore, the X-ray powder diffraction pattern of the crystalline form V has characteristic diffraction peaks at the following 2θ positions:

[0090] [Table 7]

[0091] Furthermore, for the crystalline form V, the X-ray powder diffraction pattern is essentially as shown in FIG.

[0092] Further, said crystalline form V has a DSC diagram and / or a TGA diagram in FIG.

[0093] In some embodiments, n is 0.7, X is ethylene glycol monomethyl ether, and the crystalline polymorph is crystalline form W, and the X-ray powder diffraction pattern employing Cu-Kα radiation is 6.69°±0.2°, 7.51°±0.2°, 8.31°±0.2°, 10.17°±0.2°, 12.48°±0.2°, 13.46°±0.2°, 15.03°±0.2°. It has characteristic diffraction peaks at the 2θ positions: 0.52°±0.2°, 18.28°±0.2°, 18.55°±0.2°, 22.20°±0.2°, 22.79°±0.2°, 23.17°±0.2°, 23.89°±0.2°, 24.42°±0.2°, 25.10°±0.2°, 26.65°±0.2°, 28.01°±0.2°, and 28.29°±0.2°.

[0094] Furthermore, for the crystalline form W, the X-ray powder diffraction pattern is essentially as shown in FIG.

[0095] In some embodiments, the crystalline polymorph is crystalline form X and its X-ray powder diffraction pattern employing Cu-Kα radiation has characteristic diffraction peaks at the following 2θ positions: 5.99°±0.2°, 10.52°±0.2°, 11.16°±0.2°, 12.21°±0.2°, 15.71°±0.2°, 16.41°±0.2°, 18.02°±0.2°, 19.95°±0.2°, 21.91°±0.2°, 22.32°±0.2°, and 26.05°±0.2°.

[0096] Furthermore, for said crystalline form X, the X-ray powder diffraction pattern is essentially as shown in FIG.

[0097] In some embodiments, the crystalline polymorph is crystalline form Y, and its X-ray powder diffraction pattern employing Cu-Kα radiation has characteristic diffraction peaks at the following 2θ positions: 3.21°±0.2°, 3.23°±0.2°, 7.66°±0.2°, 8.36°±0.2°, 9.08°±0.2°, 10.25°±0.2°, 12.43°±0.2°, 18.61°±0.2°, 19.03°±0.2°, 22.98°±0.2°, 23.27°±0.2°, 23.70°±0.2°, 24.92°±0.2°, and 26.13°±0.2°.

[0098] Furthermore, for the crystalline form Y, the X-ray powder diffraction pattern is essentially as shown in FIG.

[0099] In some embodiments, n is 0.9, X is DMF, and the crystalline polymorph is crystalline form Z, and its X-ray powder diffraction pattern employing Cu-Kα radiation has characteristic diffraction peaks at the following 2θ positions: 8.34°±0.2°, 10.17°±0.2°, 11.40°±0.2°, 13.51°±0.2°, 14.84°±0.2°, 18.28°±0.2°, 18.76°±0.2°, 20.16°±0.2°, 20.45°±0.2°, 20.73°±0.2°, 21.15°±0.2°, 24.71°±0.2°, 25.99°±0.2°, 26.50°±0.2°, 26.79°±0.2°, and 30.04°±0.2°.

[0100] Furthermore, for the crystalline form Z, the X-ray powder diffraction pattern is essentially as shown in FIG.

[0101] Further, said crystalline form Z has a DSC diagram and / or a TGA diagram of FIG.

[0102] The present invention further provides a pharmaceutical composition, which contains any one of the crystalline polymorphs of crystalline forms A to Z described above, and a pharma- ceutically acceptable carrier and / or excipient. In some embodiments, the pharmaceutical composition contains any one of the crystalline polymorphs of crystalline forms A, C, L, P, and V described above, and a pharma- ceutically acceptable carrier and / or excipient.

[0103] The present invention further provides a use of any one of the crystalline polymorphs A to Z or a composition containing the same in the manufacture of a medicament for treating a disease mediated by thyroid hormone receptor β. In some embodiments, the present invention provides a use of any one of the crystalline polymorphs A, C, L, P, and V or a composition containing the same in the manufacture of a medicament for treating a disease mediated by thyroid hormone receptor β.

[0104] Further, the disease mediated by the thyroid hormone receptor β is primary hypercholesterolemia.

[0105] The crystalline polymorphs of Form A through Form Z described herein are present at about 5% to about 100% by weight of the API, in some embodiments, at about 10% to about 100% by weight of the API, in some embodiments, at about 15% to about 100% by weight of the API, in some embodiments, at about 20% to about 100% by weight of the API, in some embodiments, at about 25% to about 100% by weight of the API, in some embodiments, at about 30% to about 100% by weight of the API, in some embodiments, at about 35% to about 100% by weight of the API, in some embodiments, at about 40% to about 100% by weight of the API, in some embodiments, at about 45% to about 100% by weight of the API, in some embodiments, at about 50% to about 100% by weight of the API, and in some embodiments, at about 55% to about 100% by weight of the API. In some embodiments, the API is present at about 60% to about 100% by weight of the API, in some embodiments, at about 65% to about 100% by weight of the API, in some embodiments, at about 70% to about 100% by weight of the API, in some embodiments, at about 75% to about 100% by weight of the API, in some embodiments, at about 80% to about 100% by weight of the API, in some embodiments, at about 85% to about 100% by weight of the API, in some embodiments, at about 90% to about 100% by weight of the API, in some embodiments, at about 95% to about 100% by weight of the API, in some embodiments, at about 98% to about 100% by weight of the API, in some embodiments, at about 99% to about 100% by weight of the API, and in some embodiments, essentially all of the API is essentially pure crystalline.

[0106] The present invention further provides a method for producing any one of the crystalline polymorphs of crystalline form A to crystalline form Z, the method comprising the steps of: (1) Suspension method: A crude free base of the compound of formula I (which can be prepared by the method described in WO2019240938A1) is added to a selected single solvent or a binary solvent until a suspension is formed, and the suspension is stirred at room temperature to 50°C for a certain period of time (for example, 1 h to 3 days, or 2 h to 24 h, or 2 h to 12 h, or 3 to 5 h), and then the suspension is centrifuged and dried to obtain a crystalline polymorph; or (2) Dissolution crystallization method: add a crude free base of the compound of formula I to a suitable amount of a good solvent to completely dissolve it, take a certain amount of the solution, dropwise add it to a poor solvent or dropwise add a poor solvent to the solution, stir to precipitate a solid, separate it and dry it to obtain a crystalline polymorph; or (3) Cooling method: Add the crude free base of the compound of formula I to an appropriate amount of solvent at 50-80°C until the solid is completely dissolved, and then transfer the solution to room temperature, cool it, leave it or stir it, crystallize, separate and dry to obtain a crystalline polymorph; or (4) Vapor phase diffusion method: A certain amount of the crude free base of the compound of formula I is dropped into an appropriate amount of a good solvent at room temperature to completely dissolve the sample, or the sample is mixed as a saturated solution of the good solvent, and a certain amount of the solution is taken, and the clear solution is placed in a poor solvent atmosphere and allowed to stand at room temperature until a solid precipitates, and then separated to obtain a crystalline polymorph; or (5) Thermal crystal transformation method: involves taking a certain amount of sample, placing it on a glass plate on a hot stage, heating it to the target temperature at a certain rate (e.g., 5-20°C / min, or 10-15°C / min), keeping it at a constant temperature for a while (e.g., 0.5-5 min, or 1-3 min, or 1-2 min), and then naturally cooling it to room temperature to obtain a solid.

[0107] The good solvent and the poor solvent described in the present invention are relative, and the solvent with higher solubility among a pair of solvents is the good solvent, and the solvent with lower solubility is the poor solvent. In some embodiments, the good solvent is selected from ethylene glycol methyl ether, ethylene glycol dimethyl ether, dioxane, DMF, DMSO, methanol, ethanol, n-propanol, butyl formate, 4-methyl-2-pentanone, tetrahydrofuran, isopropanol, ethyl acetate, n-heptane, ethyl ether, water, acetonitrile, toluene, chloroform, acetone, butyl formate, MTBE, and cyclohexane, which are highly soluble, and the poor solvent is selected from the above solvents, which are less soluble. In some embodiments, the good solvent is selected from ethylene glycol methyl ether, ethylene glycol dimethyl ether, dioxane, DMF, DMSO, methanol, ethanol, n-propanol, butyl formate, 4-methyl-2-pentanone, tetrahydrofuran, or a mixture thereof. In some embodiments, the anti-solvent is selected from isopropanol, ethyl acetate, n-heptane, ethyl ether, water, acetonitrile, toluene, chloroform, acetone, butyl formate, MTBE, cyclohexane, or a mixture thereof.

[0108] Unless otherwise specified, the solvents used in the above five preparation methods may be a single solvent or a combination of two or more solvents.

[0109] In some embodiments, the suspension method solvent is chloroform, in some embodiments, the suspension method solvent is tetrahydrofuran, in some embodiments, the suspension method solvent is a combination of 4-methyl-2-pentanone and cyclohexane, in some embodiments, the suspension method solvent is isopropyl acetate, in some embodiments, the suspension method solvent is acetonitrile, in some embodiments, the suspension method solvent is chloroform and ethanol, in some embodiments, the suspension method solvent is toluene, and in some embodiments, the suspension method solvent is water and DMF.

[0110] In some embodiments, the solvent employed in the elution crystallization method is ethylene glycol methyl ether and toluene, in some embodiments, the solvent employed in the elution crystallization method is DMF and water, in some embodiments, the solvent employed in the elution crystallization method is ethylene glycol monomethyl ether and acetone, in some embodiments, the solvent employed in the elution crystallization method is dioxane and ethyl ether, in some embodiments, the solvent employed in the elution crystallization method is ethylene glycol methyl ether and ethyl acetate, in some embodiments, the solvent employed in the elution crystallization method is DMSO and water, in some embodiments, the solvent employed in the elution crystallization method is dioxane and n-heptane, in some embodiments, the solvent employed in the elution crystallization method is dioxane and water, and in some embodiments, the solvent employed in the elution crystallization method is ethylene glycol dimethyl ether and chloroform.

[0111] In some embodiments, the solvent used in the temperature-lowering method is ethanol and DMSO; in some embodiments, the solvent used in the temperature-lowering method is acetonitrile and methanol; in some embodiments, the solvent used in the temperature-lowering method is ethylene glycol dimethyl ether and acetonitrile; in some embodiments, the solvent used in the temperature-lowering method is methanol and DMF; in some embodiments, the solvent used in the temperature-lowering method is toluene and methanol.

[0112] In some embodiments, the vapor phase diffusion method employs an ethylene glycol monomethyl ether solution to carry out vapor phase diffusion in ethyl ether.

[0113] The present invention has the following beneficial effects:

[0114] The crystalline form of the present invention has excellent physicochemical properties, such as good fluidity and significantly improved adhesion, which allows the crystalline form of the present invention to significantly reduce the filtration time during preparation, shorten the production cycle and save costs; the good light stability, heat stability and humidity stability of the crystalline form can ensure the reliability during storage and transportation, thereby ensuring the safety of the preparation and its efficacy after long-term storage; the crystalline form does not need special packaging treatment to prevent the effects of light irradiation, temperature and humidity, thereby reducing costs; the crystalline form will not decompose due to light irradiation, high temperature and high humidity, so patients taking the crystalline form do not need to worry about the photosensitivity reaction of the preparation due to exposure to sunlight; and the crystalline form further has high solubility, which is favorable for the dissolution of the drug and improves bioavailability.

[0115] The XRPD results of the crystalline polymorph of the present invention, especially the crystalline form C, show that it is a solid with good crystallinity and has very good stability. It has a high melting point, excellent thermal stability, the crystalline form does not undergo crystalline transformation under high temperature, high humidity, light irradiation, and accelerated conditions, and the various crystalline forms all obtain the more stable crystalline form C after crystalline transformation, and have little hygroscopicity, which is very useful as an active ingredient in pharmaceutical preparations, and is stable when stored at a temperature higher than room temperature, and is also stable during the preparation process at high temperatures.

[0116] As can be appreciated, differential scanning calorimetry (DSC) is well known in the art, and the height of the melting peak in a DSC curve depends on many factors related to sample preparation and instrument geometry, and the peak position is relatively insensitive to experimental details. Therefore, in some embodiments, the crystalline compounds of the present invention are required to have a DSC pattern with a characteristic peak position and have substantially the same properties as the DSC pattern according to the drawings of the present invention, with a measurement error tolerance within ±5°C, typically within ±3°C.

[0117] As will be understood, the numerical values ​​described and protected by this invention are approximations, and variations in the numerical values ​​can be due to instrument calibration, instrument error, crystal purity, crystal size, sample size, and other factors.

[0118] As can be understood, the crystalline forms of the present invention are not limited to those with characteristic spectra, e.g., XRPD, DSC, TGA, DVS, isothermal adsorption curve diagrams, that are exactly the same as those depicted in the figures disclosed in the present invention, and any crystalline form having characteristic spectra that are basically the same or essentially the same as those depicted in the figures is within the scope of the present invention.

[0119] A "therapeutically effective amount" is an amount of a compound that elicits a physiological or medical response in a tissue, system, or subject, which is desired, and includes an amount of the compound that, when administered to a subject, is sufficient to prevent the occurrence of, or to alleviate to some extent, one or more symptoms of the disease or condition being treated.

[0120] "Room temperature": 10℃~30℃.

[0121] The term "carrier" refers to a system that does not significantly stimulate the living body, does not eliminate the biological activity and properties of a given compound, and can change the administration form and distribution of a drug in the human body, control the release rate of the drug, and deliver the drug to a target organ. Non-limiting examples include microcapsules and microspheres, nanoparticles, liposomes, etc.

[0122] "Excipient" refers to a substance that is not a therapeutic agent itself, but is added to a pharmaceutical composition as a diluent, adjuvant, adhesive and / or vehicle to improve its processing or storage properties, or to permit or facilitate the compound or pharmaceutical composition to form a dosage form for administration. As known to those skilled in the art, pharmaceutical excipients can serve a variety of functions and may be described as wetting agents, buffers, suspending aids, lubricants, emulsifiers, disintegrants, absorbents, preservatives, surfactants, colorants, flavoring agents and sweeteners. Examples of pharmaceutical excipients include, but are not limited to, the following: (1) sugars, such as lactose, glucose, and sucrose; (2) starches, such as corn starch and potato starch; (3) cellulose and its derivatives, such as sodium carboxymethylcellulose, ethylcellulose, cellulose acetate, hydroxypropyl methylcellulose, hydroxypropyl cellulose, microcrystalline cellulose, and crosslinked carboxymethylcellulose (e.g., crosslinked sodium carboxymethylcellulose); (4) tragacanth gum powder; (5) malt; (6) gelatin; (7) talc; (8) excipients. excipients, such as cocoa butter, suppository waxes, (9) oils, such as peanut oil, cottonseed oil, safflower oil, sesame oil, olive oil, corn oil, and soybean oil, (10) glycols, such as propylene glycol, (11) polyols, such as glycerin, sorbitol, mannitol, and polyethylene glycol, (12) esters, such as ethyl oleate and ethyl laurate, (13) agar, (14) buffers, such as magnesium hydroxide and aluminum hydroxide, (15) alginic acid, (16) water for endotoxin testing, (17) isotonic saline, (18) Ringer's solution, (19) ethanol, (20) pH buffer solutions, (21) polyesters, polycarbonates, and / or polyanhydrides, and (22) other non-toxic, compatible substances used in drug formulations.

[0123] "Crystal form" or "crystal" or "crystalline polymorph" refers to any solid material that exhibits three-dimensional arrangement and, in contrast to an amorphous solid material, produces a characteristic XRPD pattern with well-defined peaks.

[0124] "X-ray powder diffraction pattern (XRPD pattern)" refers to an experimentally observed diffraction pattern or parameters, data, or values ​​derived therefrom. XRPD patterns are typically characterized by peak positions (abscissa) and / or peak intensities (ordinate).

[0125] "2θ" refers to the peak position, expressed in degrees (°), set up in an X-ray diffraction experiment, and is typically the abscissa unit in a diffraction pattern. If a reflection is diffracted when the incident beam makes a θ angle with a lattice plane, then the experimental set up requires recording the reflected beam at 2θ angles. It should be understood that the specific 2θ values ​​of a particular crystalline form referred to herein are intended to represent 2θ values ​​(expressed in degrees) measured using the X-ray diffraction experimental conditions described herein.

[0126] The terms "essentially the same" or "essentially as shown in Figure XX" for X-ray diffraction peaks are meant to take into account the typical peak position and intensity variations. For example, as one of ordinary skill in the art would understand, the peak positions (2θ) will show some variation, typically up to 0.1-0.2°, and the instrument used to measure the diffraction will also produce some variation. Also, as one of ordinary skill in the art would understand, the relative peak intensities will vary depending on the instrumental differences and the degree of crystallinity, preferred orientation, sample surface prepared, and other factors known to one of ordinary skill in the art, and should be considered merely a qualitative measurement. [Brief description of the drawings]

[0127] [Figure 1] 1 is an X-ray powder diffraction pattern of crystalline form A of the compound of formula I. [Diagram 2] 1 is a differential scanning calorimetry analysis curve and a thermogravimetric analysis pattern of the crystalline form A of the compound of formula I. [Diagram 3] 1 is an X-ray powder diffraction pattern of crystalline form B of the compound of formula I. [Figure 4] 1 is a differential scanning calorimetry analysis curve and a thermogravimetric analysis pattern of the crystalline form B of the compound of formula I. [Diagram 5]1 is an X-ray powder diffraction pattern of crystalline form C of the compound of formula I. [Figure 6] 1 is a differential scanning calorimetry analysis curve and a thermogravimetric analysis pattern of the crystalline form C of the compound of formula I. [Figure 7] 1 is an X-ray powder diffraction pattern of crystalline form D of the compound of formula I. [Figure 8] 1 is a differential scanning calorimetry analysis curve and a thermogravimetric analysis pattern of the crystalline form D of the compound of formula I. [Figure 9] 1 is an X-ray powder diffraction pattern of crystalline form E of the compound of formula I. [Figure 10] 1 is a differential scanning calorimetry analysis curve and a thermogravimetric analysis pattern of the crystalline form E of the compound of formula I. [Figure 11] 1 is an X-ray powder diffraction pattern of crystalline form F of the compound of formula I. [Figure 12] 1 is a differential scanning calorimetry analysis curve and a thermogravimetric analysis pattern of the crystalline form F of the compound of formula I. [Figure 13] 1 is an X-ray powder diffraction pattern of crystalline form G of the compound of formula I. [Figure 14] 1 is a differential scanning calorimetry analysis curve and a thermogravimetric analysis pattern of the crystalline form G of the compound of formula I. [Figure 15] 1 is an X-ray powder diffraction pattern of crystalline form H of the compound of formula I. [Figure 16] 1 is a differential scanning calorimetry analysis curve and a thermogravimetric analysis pattern of the crystalline form H of the compound of formula I. [Figure 17] 1 is an X-ray powder diffraction pattern of crystalline form I of the compound of formula I. [Figure 18] 1 is a differential scanning calorimetry analysis curve and a thermogravimetric analysis pattern of the crystalline form I of the compound of formula I. [Figure 19] 1 is an X-ray powder diffraction pattern of crystalline form J of the compound of formula I. [Figure 20] 1 is a differential scanning calorimetry analysis curve and a thermogravimetric analysis pattern of the crystalline form J of the compound of formula I. [Figure 21]1 is an X-ray powder diffraction pattern of crystalline form K of the compound of formula I. [Figure 22] 1 is a differential scanning calorimetry analysis curve and a thermogravimetric analysis pattern of the crystalline form K of the compound of formula I. [Figure 23] 1 is an X-ray powder diffraction pattern of crystalline form L of the compound of formula I. [Figure 24] 1 is a differential scanning calorimetry analysis curve and a thermogravimetric analysis pattern of the crystalline form L of the compound of formula I. [Diagram 25] 1 is an X-ray powder diffraction pattern of crystalline form M of the compound of formula I. [Figure 26] 1 is a differential scanning calorimetry analysis curve and a thermogravimetric analysis pattern of the crystalline form M of the compound of formula I. [Figure 27] 1 is an X-ray powder diffraction pattern of crystalline form N of the compound of formula I. [Figure 28] 1 is a differential scanning calorimetry analysis curve and a thermogravimetric analysis pattern of the crystalline form N of the compound of formula I. [Figure 29] 1 is an X-ray powder diffraction pattern of crystalline form O of the compound of formula I. [Diagram 30] 1 is a differential scanning calorimetry analysis curve and a thermogravimetric analysis pattern of the crystalline form O of the compound of formula I. [Diagram 31] 1 is an X-ray powder diffraction pattern of crystalline form P of the compound of formula I. [Diagram 32] 1 is a differential scanning calorimetry analysis curve and a thermogravimetric analysis pattern of the crystalline form P of the compound of formula I. [Diagram 33] 1 is an X-ray powder diffraction pattern of crystalline form Q of the compound of formula I. [Diagram 34] 1 is a differential scanning calorimetry analysis curve and a thermogravimetric analysis pattern of the crystalline form Q of the compound of formula I. [Diagram 35] 1 is an X-ray powder diffraction pattern of crystalline form R of the compound of formula I. [Diagram 36] 1 is a differential scanning calorimetry analysis curve and a thermogravimetric analysis pattern of the crystalline form R of the compound of formula I. [Figure 37]1 is an X-ray powder diffraction pattern for crystalline form S of the compound of formula I. [Figure 38] 1 is a differential scanning calorimetry analysis curve and a thermogravimetric analysis pattern of the crystalline form S of the compound of formula I. [Figure 39] 1 is an X-ray powder diffraction pattern of crystalline form T of the compound of formula I. [Diagram 40] 1 is a differential scanning calorimetry analysis curve and a thermogravimetric analysis pattern of the crystalline form T of the compound of formula I. [Diagram 41] 1 is an X-ray powder diffraction pattern of crystalline form U of the compound of formula I. [Diagram 42] 1 is a differential scanning calorimetry analysis curve and a thermogravimetric analysis pattern of the crystalline form U of the compound of formula I. [Diagram 43] 1 is an X-ray powder diffraction pattern of crystalline form V of the compound of formula I. [Diagram 44] 1 is a differential scanning calorimetry analysis curve and a thermogravimetric analysis pattern of the crystalline form V of the compound of formula I. [Diagram 45] 1 is an X-ray powder diffraction pattern of crystalline form W of the compound of formula I. [Diagram 46] 1 is an X-ray powder diffraction pattern of crystalline form X of the compound of formula I. [Figure 47] 1 is an X-ray powder diffraction pattern of crystalline form Y of the compound of formula I. [Figure 48] 1 is an X-ray powder diffraction pattern of crystalline form Z of the compound of formula I. [Figure 49] 1 is a differential scanning calorimetry analysis curve and a thermogravimetric analysis pattern of the crystalline form Z of the compound of formula I. [Figure 50] This is the DVS pattern of crystal form C. [Figure 51] 1 is an X-ray powder diffraction pattern for stability study of crystalline form C. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0128] The present invention will be described in detail below with reference to examples. Unless specific conditions are specified in the examples, the experiments were carried out according to general conditions. The examples given are for better illustrating the present invention, and it should be understood that the present invention is not limited to the examples given. Non-essential improvements and adjustments made to the embodiments by those skilled in the art based on the above invention still fall within the scope of protection of the present invention.

[0129] The structures of the compounds were confirmed by nuclear magnetic resonance (NMR) and / or mass spectrometry (MS). NMR displacements (δ) are given in units of 10-6 (ppm). NMR measurements were performed using nuclear magnetometers (Bruker Avance III 400 and Bruker Avance 300), with the solvents being deuterated dimethylsulfoxide (DMSO-d6), deuterated chloroform (CDCl3), and deuterated methanol (CD3OD), and the internal standard was tetramethylsilane (TMS).

[0130] MS measurements were performed using Agilent 6120B (ESI) and Agilent 6120B (APCI).

[0131] HPLC measurements were performed using an Agilent 1260DAD high pressure liquid chromatograph (Zorbax SB-C18 100×4.6 mm).

[0132] XRPD measurements were performed using a Bruker D8 Advance X-ray powder diffractometer (Bruker, GER). The 2θ scanning angle was 3° to 45°, the scanning step size was 0.02°, and the exposure time was 0.12 seconds. When the samples were tested, the voltage and current of the light tube were 40 kV and 40 mA, respectively, and the sample disk was a zero-background sample disk.

[0133] The model number of the TA used for the TGA measurements was TA Discovery 55 (TA, US). 2-5 mg of sample was placed in an equilibrated open-type aluminum sample disk and automatically weighed in the TGA furnace. The sample was heated to the final temperature at a rate of 10 °C / min, and the nitrogen gas purge rate at the sample was 60 mL / min and the nitrogen gas purge rate at the balance was 40 mL / min.

[0134] The model number of the TA used for the DSC measurements was TA Discovery 2500 (TA, US). After accurately weighing 1–2 mg of sample, it was placed in a perforated DSC Tzero sample disk and heated to the final temperature at a rate of 10 °C / min, and the nitrogen gas purge rate in the furnace was 50 mL / min.

[0135] The known starting materials of the present invention may be synthesized by adopting or following known methods in the art (for example, the methods in Patent WO2019240938A1), or may be purchased from companies such as Taitan Technology, Ananji Chemical, Shanghai Demo, Chengdu Kelong Chemical, Shaoyuan Chemical Technology, and Bailingwei Technology.

[0136] Example 1 Preparation of Crude Free Base of Compound I [ka]

[0137] Step 1: Preparation of compound b N-(3,5-dichloro-4-((7-(methyl-d3)-1-oxo-2,5,6,7-tetrahydro-1H-cyclopentane[d]pyridazin-4-yl)oxy)phenyl)benzamide (1H) N-(3,5-dichloro-4-((7-(methyl-d3)-1-oxo-2,5,6,7-tetrahydro-1H-cyclopenta[d]pyridazin-4-yl)oxy)phenyl)benzamid [ka] 4.62 kg of compound a was dissolved in 25.0 L of glacial acetic acid and added to a 100 L reaction vessel, 3300 g of benzoic anhydride was added, stirring was started, and the mixture was reacted at room temperature for about 4 hours. TLC (n-hexane / ethyl acetate=5 / 1) was used to monitor until compound a disappeared. Then, 2722 g of anhydrous sodium acetate was added, the mixture was heated to 120°C, stirred, and reacted for about 18 hours. The reaction liquid is cooled to 60-65°C, concentrated under reduced pressure to remove most of the acetic acid, and after the concentration is completed, 10L of anhydrous ethanol is added to the residual liquid and mixed uniformly, and the mixed solution is slowly added to 250L of water, and the stirring is kept rapid during the addition process, and a large amount of solid is precipitated during the addition process. After the addition, stirring is continued for about 0.5 hours, centrifuged, and the filter cake is washed with purified water (20L x 2) to obtain compound b, the yield is 100%, and directly proceeded to the next step. 1H NMR(400MHz,DMSO)δ 12.07(s,1H),10.55(s,1H),8.04(s,2H),7.98-7.95(m,2H),7.63-7.50(m,3H) ),3.29-3.25(m,1H),3.02-2.90(m,2H),2.39-2.36(m,1H),1.75-1.72(m,1H). LCMS m / z=433.1 [M+1]+

[0138] Step 2: Preparation of compound c 4-(4-amino-2,6-dichlorophenoxy)-7-(methyl-d3)-2,5,6,7-tetrahydro-1H-cyclopentyl[d]pyridazin-1-one 4-(4-amino-2,6-dichlorophenoxy)-7-(methyl-d3)-2,5,6,7-tetrahydro-1H-cyclopenta[d]pyridazin-1-one [ka] In a 100L reactor, add 5.76kg of compound b, which is the crude product from the previous step, potassium hydroxide solution (2606g of KOH dissolved in 19.5L of purified water) and 6.0L of anhydrous ethanol while stirring, and after completion, heat and reflux the reaction for about 16 hours to complete the reaction of the center control raw material. The temperature was lowered to 25°C, 30L of water was added, the pH was adjusted to 8-9 with solid ammonium chloride, 35.0L of ethyl acetate was added, the mixture was stirred and separated, the aqueous phase was extracted with ethyl acetate (15.0L x 2), the organic phase was combined, washed with 5% aqueous sodium chloride solution (25L x 2), the organic phase was dried over 3.0Kg of anhydrous sodium sulfate, filtered, and the organic phase was concentrated until no clear fraction was flowing out to obtain a crude product. The crude product was dissolved in 7.0 L of a dioxane solution containing 10% water by heating, cooled to room temperature, stirred and crystallized for about 16 hours, filtered to obtain a wet product, which was further purified twice and vacuum dried at 50°C for about 12 hours to obtain compound c1507g. 1H NMR(400MHz,DMSO)δ 11.98(s,1H),6.67(m,2H),5.60(s,2H),3.30-3.19(m,1H),3.03-2.93(m,1H),2.90-2.70(m,1H),2.35(m,1H),1.69(m,1H). LCMS m / z=329.0 [M+1]+

[0139] Step 3: Preparation of compound d (R)-4-(4-amino-2,6-dichlorophenoxy)-7-(methyl-d3)-2,5,6,7-tetrahydro-1H-cyclopentyl[d]pyridazin-1-one (R)-4-(4-amino-2,6-dichlorophenoxy)-7-(methyl-d3)-2,5,6,7-tetrahydro-1H-cyclopenta[d]pyridazin-1-one [ka] 3298g of racemic compound c was taken and used for chiral separation. After separation, Compound d (retention time: 1.583 min, 1230 g, off-white solid, ee%=99.60%, yield 37.3%), Two optical isomers were obtained, compound d-1 (retention time: 1.926 min, 1255 g, off-white solid, ee%=99.76%, yield 38.1%). The division conditions are as follows: Instrument: MG III preparative SFC, Column: Whelk O1(S,S), 300×50mm ID, 10μm, Mobile phase: A: CO2, B: methanol, gradient: B 40%, flow rate: 200mL / min, back pressure: 100bar; Column temperature: 38℃, wavelength: 220nm, cycle: 4.5min, sample preparation: the racemate was dissolved in methanol / dichloromethane to obtain 50mg / ml, injection: 17ml / time. compound d 1H NMR(400MHz,DMSO)δ 11.98(s,1H),6.67(s,2H),5.60(s,2H),3.30-3.19(m,1H),3.03-2.93(m,1H),2.90-2.70(m,1H),2.35(dtd,1H),1.69(ddt,1H). LCMS m / z=329.1 [M+1]+ Compound d-1 1H NMR(400MHz,DMSO)δ 11.98(s,1H),6.68(d,2H),5.60(s,2H),3.29-3.18(m,1H),2.97(tdd,1H),2.90-2.72(m,1H),2.35(dtd,1H),1.69(ddt,1H). LCMS m / z=329.0 [M+1]+

[0140] Step 4: Preparation of compound e (R,Z)-(2-cyano-2-(2-(3,5-dichloro-4-)((7-(methyl-d3)-1-oxo-2,5,6,7-tetrahydro-1H-cyclopentyl[d]pyridazin-4-yl)oxy)phenyl)hydrazono-4-acetyl)carbamic acid ethyl ester Ethyl (R,Z)-(2-cyano-2-(2-(3,5-dichloro-4-((7-(methyl-d3)-1-oxo-2,5,6,7-tetrahydro-1H-cyclopenta[d]pyridazin-4-yl)oxy)phenyl)hydrazineylidene)acetyl)carbamate [ka] In a 100L reaction vessel, 16.0 kg of acetic acid, 4.0 kg of purified water and 2.0 kg of compound d were added while stirring. The temperature was lowered to 0±5°C, and 2.36 kg of hydrochloric acid was added. After completion, the mixture was kept at 0±5°C and stirred for about 20 minutes. The temperature was controlled at 0±5°C, and sodium nitrite solution (0.5 kg of sodium nitrite dissolved in 1.0 kg of purified water) was added dropwise. After completion of the dropwise addition, the mixture was kept at 0±5°C and reacted for 2 hours. The temperature was controlled at 5±5°C, and sodium acetate solution (1.5 kg of sodium acetate dissolved in 6.0 kg of purified water) was added dropwise. After the addition was completed, 0.99 kg of N-cyanoacetylurethane was added. After the addition was completed, the temperature was raised to 10±5°C, and the reaction was carried out for about 2 hours, after which sampling was carried out to monitor by HPLC. Thereafter, sampling was carried out every about 2 hours, and the content of compound d was detected as ≦1.0% by HPLC, and the reaction was stopped. After the reaction is completed, the temperature is controlled at 10±5°C, 30.0 kg of purified water is added to the reactor, and after completion, the temperature is controlled at 10±5°C, stirring is continued for 1 hour, filtration is performed, and the filter cake is washed with 3.0 kg of purified water. The filter cake and 12.6 kg of anhydrous ethanol are added to a 100L reactor, the temperature is raised to 50±5°C, and stirring is performed for about 1 hour. The temperature is lowered to 20±5°C, stirring is performed for 0.5 hours, filtration is performed, and the filter cake is washed once with 1.26 kg of anhydrous ethanol. The filter cake was dried at 55±5° C. and vacuum≦−0.07 MPa for about 17 hours to obtain compound e, which weighed 2.6327 kg. 1H NMR(400MHz,DMSO)δ 12.08(d,2H),10.88(s,1H),7.99(s,2H),4.21(q,2H),3.30-3.17(m,1H),3.08- 2.95(m,1H),2.95-2.80(m,1H),2.38(ddd,1H),1.78-1.63(m,1H),1.28(t,3H). LCMS m / z=496.1 [M+1]+

[0141] Step 5: Preparation of Compounds of Formula I (R)-2-(3,5-dichloro-4-((7-(methyl-d3)-1-oxo-2,5,6,7-tetrahydro-1H-cyclopenta[d]pyridazin-4-yl)oxy)phenyl)-3,5-dioxo-2,3,4,5-tetrahydro-1,2,4-triazine-6-carbonitrile (R)-2-(3,5-dichloro-4-((7-(methyl-d3)-1-oxo-2,5,6,7-tetrahydro-1H-cyclopenta[d]pyridazin-4-yl)oxy)phenyl)-3,5-dioxo-2,3,4,5-tetrahydro-1,2,4-triazine-6-carbonitrile [ka] In a 100L reactor, 12.40kg of N,N-dimethylacetamide, 2.6269kg of compound e and 0.54kg of sodium acetate were added while stirring. After completion, the temperature was raised and the internal temperature was kept at 115±5°C. After reacting for about 2 hours, sampling was performed to monitor by HPLC, and then sampling was performed every about 2 hours, and the content of compound e was detected as ≦1.0% by HPLC, and the reaction was stopped. After the reaction was completed, the temperature was lowered to 60±5°C, 0.788 kg of purified water was added to the reaction solution, and after completion, the reaction solution was filtered while still hot, and the reaction solution was quickly added to 13.66 kg of purified water, and the temperature was lowered to 10±5°C. After filtration, the filter cake was added to 20 L of dimethyl sulfoxide, heated to dissolve, 800 L of acetone was added, stirred for 0.5-1 h, filtered, and the filter cake was dried at 55±5°C and vacuum ≦-0.07 MPa for about 20 hours to obtain the amorphous compound of formula (I), weighing 1.56 kg. 1H NMR(400MHz,DMSO)δ 13.26(s,1H),12.09(s,1H),7.79(s,2H),3.32-3.24(m,1H),3.10-2.99(m,1H),2.96-2.88(m,1H),2.45-2.31(m,1H),1.77-1.69(m,1H). LCMS m / z=450.0 [M+1]+.

[0142] Example 2 Preparation of Crystalline Form A of the Compound of Formula I 200 mg of the compound of formula I prepared in Example 1 was taken, 10 ml of water was added, stirred at room temperature for 3-5 h, and filtered to obtain crystalline form A. The crystalline form A of the compound of formula I was characterized by XRPD, DSC and TGA, the XRPD diagram is shown in FIG. 1, and the DSC and TGA diagrams are shown in FIG. 2. The TGA result showed that the crystalline form A had a weight loss of 7.4% during heating to 130°C, and decomposed above 315°C. The DSC result showed that the crystalline form A had an endothermic signal around 99°C corresponding to the weight loss of TGA, and a crystalline transformation exothermic peak around 171°C. The thermal crystal transformation experiment showed that the crystalline form A was still crystalline form A when heated to 150°C, and transformed into crystalline form C when heated to 300°C. The NMR result showed that there was no solvent remaining in the sample. The water content test result showed that the water content of Form A was 8.2%, which was consistent with the weight loss of TGA. In summary, Form A was a dihydrate.

[0143] The peak positions of the XRPD diffraction peaks of crystalline form A are shown in the table below.

[0144] [Table 8]

[0145] Example 3 Preparation of Crystalline Form B of Compound of Formula I About 150 mg of the compound of formula I prepared in Example 1 was taken, 4-methyl-2-pentanone was added until it was dissolved, n-hexane was added dropwise until a solid was precipitated, and the mixture was stirred for 3-5 h, filtered, and the solid was dried at room temperature overnight to obtain crystalline form B. The crystalline form B of the compound of formula I was characterized by XRPD, DSC, and TGA. The XRPD diagram is shown in FIG. 3, and the DSC and TGA diagrams are shown in FIG. 4. The TGA results showed that the crystalline form B had a weight loss of 8.8% during heating to 200°C, and may decompose above 315°C. The DSC results showed that the crystalline form B had an endothermic signal corresponding to a weight loss around 139°C. According to the NMR results, the structure of the compound did not change, and the solvent peak of cyclohexane was observed at 1.40 ppm, and the solvent peaks of 4-methyl-2-pentanone were observed at 0.85 ppm, 1.99 ppm, 2.06 ppm and 2.30 ppm. The ratio of the compound to cyclohexane was calculated from the integration results as 1:0.05, the ratio of the compound to 4-methyl-2-pentanone was 1:0.4, and the crude estimated mass occupancy of 4-methyl-2-pentanone was about 8.5%, which was consistent with the weight loss of TGA. In summary, crystalline form B is a solvate of 4-methyl-2-pentanone, and the ratio of the compound to 4-methyl-2-pentanone was 1:0.4.

[0146] The peak positions of the XRPD diffraction peaks of crystalline form B are shown in the table below.

[0147] [Table 9]

[0148] Example 4 Preparation of Crystalline Form C of the Compound of Formula I About 150 mg of the compound of formula I prepared in Example 1 was taken, and 3.0 mL of chloroform was added, stirred at 50°C for 1 day, centrifuged, and the resulting solid was dried under vacuum at room temperature overnight to obtain crystalline form C. The crystalline form C of the compound of formula I was characterized by XRPD, DSC and TGA, and the XRPD diagram is shown in Figure 5, and the DSC and TGA diagrams are shown in Figure 6. The TGA result showed that the crystalline form C had a weight loss of 0.8% during heating to 200°C, and may decompose above 315°C. The DSC result showed that the crystalline form C had an endothermic signal around 70°C corresponding to the weight loss of TGA, and no melting endothermic signal was observed before 300°C. In summary, the crystalline form C was an anhydrous crystalline form.

[0149] The peak positions of the XRPD diffraction peaks of crystalline form C are shown in the table below.

[0150] [Table 10]

[0151] Example 5 Preparation of Crystalline Form D of the Compound of Formula I 20 mg of the compound of formula I prepared in Example 1 was taken, ethylene glycol monomethyl ether was added until it was dissolved, toluene was added dropwise until a solid was precipitated, and the mixture was stirred for 3-5 h, centrifuged, and the solid obtained was vacuum dried at room temperature overnight to obtain crystalline form D. The crystalline form D of the compound of formula I was characterized by XRPD, DSC and TGA, and the XRPD diagram is shown in FIG. 7, and the DSC and TGA diagrams are shown in FIG. 8. The TGA results showed that the crystalline form D had a weight loss of 7.6% during heating to 150°C, a weight loss of 8.5% between 150 and 200°C, and may decompose above 330°C. The DSC results showed that the crystalline form D had endothermic peaks at around 139°C and 177°C corresponding to weight loss. According to the NMR results, the structure of the compound did not change, and toluene solvent peaks were observed at 2.30 ppm, 7.18 ppm, and 7.24 ppm. The crude estimated mass fraction calculated from the integration results was about 14.0%, which was consistent with the weight loss measured by TGA. In summary, crystalline form D is a toluene solvate, and the ratio of the compound to toluene was 1:0.4.

[0152] The peak positions of the XRPD diffraction peaks of crystalline form D are shown in the table below.

[0153] [Table 11]

[0154] Example 6 Preparation of Crystalline Form E of the Compound of Formula I 55 mg of the compound of formula I prepared in Example 1 was taken, N,N-dimethylformamide (DMF) was added until it was dissolved, water was added dropwise until a solid was precipitated, and the mixture was stirred for 3-5 h, centrifuged, and the obtained solid was vacuum dried at room temperature overnight to obtain crystalline form E. The crystalline form E of the compound of formula I was characterized by XRPD, DSC and TGA, and the XRPD diagram is shown in FIG. 9, and the DSC and TGA diagrams are shown in FIG. 10. The TGA results showed that crystalline form E had a weight loss of 10.2% during heating to 120°C, a weight loss of 11.2% between 120 and 180°C, and may decompose above 330°C. The DSC results showed that crystalline form E had endothermic peaks around 112°C and 157°C corresponding to the weight loss of TGA. The thermal crystal transformation experiment results showed that crystalline form E was transformed into crystalline form C after desolvation. NMR results showed that the structure of the compound was unchanged, and DMF solvent peaks were observed at 2.73 ppm, 2.89 ppm, and 7.95 ppm. The crude mass occupancy was estimated to be about 20.5% based on the integration results, which was consistent with the weight loss measured by TGA. In summary, crystalline form E is a DMF solvate, and the ratio of the compound to DMF was 1:0.8.

[0155] The peak positions of the XRPD diffraction peaks of crystalline form E are shown in the table below.

[0156] [Table 12]

[0157] Example 7 Preparation of Crystalline Form F of the Compound of Formula I 20 mg of the compound of formula I prepared in Example 1 was taken, ethylene glycol methyl ether was added until it was dissolved, acetone was added dropwise until a solid was precipitated, and the mixture was stirred for 3-5 h, centrifuged, and the obtained solid was dried overnight under vacuum at room temperature to obtain crystalline form F. The crystalline form F of the compound of formula I was characterized by XRPD, DSC and TGA, and the XRPD diagram is shown in FIG. 11, and the DSC and TGA diagrams are shown in FIG. 12. The TGA result showed that the crystalline form F had a weight loss of 11.3% during heating to 150°C, and may decompose above 330°C. The DSC result showed that the crystalline form F had an endothermic signal corresponding to the weight loss of TGA at around 125-180°C, and a heat dissipation peak of crystalline transformation at around 204°C. The experimental results of thermal crystalline transformation showed that the crystalline form F was transformed into crystalline form C after heating to 230°C. According to the NMR results, the structure of the compound did not change, and the solvent peak of acetone was observed at 2.09 ppm. The crude estimated mass fraction calculated from the integration results was about 10.0%, which was consistent with the weight loss by TGA. In summary, crystalline form F is an acetone solvate, and the ratio of the compound to acetone was 1:1.

[0158] The peak positions of the XRPD diffraction peaks of crystalline form F are shown in the table below.

[0159] [Table 13]

[0160] Example 8 Preparation of Crystalline Form G of the Compound of Formula I 20 mg of the compound of formula I prepared in Example 1 was taken, ethylene glycol methyl ether was added until it dissolved, ethyl acetate was added dropwise until a solid was precipitated, and the mixture was stirred for 3-5 h, centrifuged, and the solid obtained was vacuum dried at room temperature overnight to obtain crystalline form G. The crystalline form G of the compound of formula I was characterized by XRPD, DSC, and TGA, and the XRPD diagram is shown in FIG. 13, and the DSC and TGA diagrams are shown in FIG. 14. The TGA result showed that the crystalline form G had a weight loss of 16.2% during heating to 200°C, and may decompose after 330°C. The DSC result showed that the crystalline form G had an endothermic signal around 152°C corresponding to the weight loss of TGA. The NMR result showed that the structure of the compound did not change, and the solvent peaks of ethyl acetate were observed at 1.16 ppm, 1.99 ppm, and 4.03 ppm. The crude estimated mass occupancy was about 15.0% as calculated from the integration result, which was consistent with the weight loss of TGA. In summary, crystalline form G was an ethyl acetate solvate, and the ratio of the compound to ethyl acetate was 1:1.

[0161] The peak positions of the XRPD diffraction peaks of crystalline form G are shown in the table below.

[0162] [Table 14-1] [Table 14-2]

[0163] Example 9 Preparation of Crystalline Form H of the Compound of Formula I 55 mg of the compound of formula I prepared in Example 1 was taken, dimethyl sulfoxide was added until it was dissolved, water was added dropwise until a solid was precipitated, and the mixture was stirred for 3-5 h, centrifuged, and the obtained solid was dried overnight under vacuum at room temperature to obtain crystalline form H. The crystalline form H of the compound of formula I was characterized by XRPD, DSC and TGA, and the XRPD diagram is shown in FIG. 15, and the DSC and TGA diagrams are shown in FIG. 16. The TGA result showed that the crystalline form H had a weight loss of 15.2% during heating to 210°C, and may decompose after 320°C. The DSC result showed that the crystalline form H had an endothermic signal at 160-230°C corresponding to the weight loss of TGA. The NMR result showed that the structure of the compound was unchanged, and a DMSO solvent peak was observed at 2.54 ppm. The crude estimated mass occupancy was calculated from the integration result to be about 15.0%, which was consistent with the weight loss of TGA. In summary, crystalline form H was a DMSO solvate, and the ratio of the compound to DMSO was 1:1.

[0164] The peak positions of the XRPD diffraction peaks of crystalline form H are shown in the table below.

[0165] [Table 15]

[0166] Example 10 Preparation of Crystalline Form I of the Compound of Formula I 55 mg of crystalline form A of the compound of formula I was taken, and isopropyl acetate was added, stirred at 50°C for 10-15 h, centrifuged, and the obtained solid was vacuum dried at room temperature overnight to obtain crystalline form I. The crystalline form I of the compound of formula I was characterized by XRPD, DSC, and TGA, as shown in Figures 17-18, respectively. The TGA results showed that the crystalline form I had a weight loss of 17.7% during heating to 200°C, and may decompose after 315°C. The DSC results showed that the crystalline form I had one endothermic peak around 158°C, which corresponds to the weight loss of TGA. The NMR results showed that the structure of the compound was unchanged, and the solvent peaks of isopropyl acetate were observed at 1.17 ppm, 1.96 ppm, and 4.84 ppm. The crude estimated mass occupancy was about 17.6% as calculated from the integration results, which was consistent with the weight loss of TGA. In summary, crystalline form I was an isopropyl acetate solvate, and the ratio of the compound to isopropyl acetate was 1:0.9.

[0167] The peak positions of the XRPD diffraction peaks of crystalline Form I are shown in the table below.

[0168] [Table 16-1] [Table 16-2]

[0169] Example 11 Preparation of Crystal Form J of the Compound of Formula I 55 mg of crystalline form A of the compound of formula I was taken, acetonitrile was added, and the mixture was stirred at 50°C for 10-15 h, centrifuged, and the solid obtained was vacuum dried at room temperature overnight to obtain crystalline form J. The crystalline form J of the compound of formula I was characterized by XRPD, DSC, and TGA, as shown in Figures 19-20, respectively. The TGA results showed that crystalline form J had a 4.1% weight loss during heating to 150°C, and may decompose after 320°C. The DSC results showed that crystalline form J had one endothermic signal corresponding to the weight loss of TGA at around 133°C, and a heat dissipation signal of crystal transformation at around 157°C. The experimental results of thermal crystal transformation showed that crystalline form J was transformed into crystalline form C after desolvation. The NMR results showed that the structure of the compound did not change, and the solvent peak of acetonitrile was observed at 2.07 ppm. The ratio of the compound to acetonitrile was calculated to be 1:0.1 from the integration results, and the crude estimated mass occupancy was about 1.29%.

[0170] Example 12 Preparation of Crystal Form K of the Compound of Formula I 55 mg of the compound of formula I prepared in Example 1 was taken, dioxane was added until it dissolved, n-heptane was added dropwise until a solid precipitated, and the mixture was stirred for 3-5 h, centrifuged, and the obtained solid was vacuum dried at room temperature overnight to obtain crystalline form K. The crystalline form K of the compound of formula I was characterized by XRPD, DSC, and TGA, as shown in Figures 21-22, respectively. The TGA results showed that the crystalline form K had a weight loss of 15.6% during heating to 210°C, and may decompose after 315°C. The DSC results showed that the crystalline form K had an endothermic signal around 185-205°C corresponding to the weight loss of TGA, and a recrystallization exothermic peak around 254°C. The experimental results of thermal crystal conversion showed that the crystalline form K was converted to crystalline form C after heating to 260°C. According to the NMR results, the structure of the compound did not change, and a dioxane solvent peak was observed at 3.57 ppm. The crude estimated mass fraction calculated from the integration results was about 14.3%, which was consistent with the weight loss in TGA. In summary, the crystalline form K was a dioxane solvate, and the ratio of the compound to dioxane was 1:0.9.

[0171] The peak positions of the XRPD diffraction peaks of crystalline form K are shown in the table below.

[0172] [Table 17]

[0173] Example 13 Preparation of Crystalline Form L of the Compound of Formula I 40 mg of the compound of formula I prepared in Example 1 was taken, dioxane was added until it dissolved, water was added dropwise until a solid precipitated, and the mixture was stirred for 3-5 h, centrifuged, and the obtained solid was vacuum dried at room temperature overnight to obtain crystalline form L. The crystalline form L of the compound of formula I was characterized by XRPD, DSC, and TGA, as shown in Figures 23-24, respectively. The TGA results showed that the crystalline form L had a weight loss of 7.3% during heating to 100°C, and may decompose after 330°C. The DSC results showed that the crystalline form L had an endothermic peak around 80°C corresponding to the weight loss of TGA, and a heat dissipation peak of crystalline transformation around 158°C. The experimental results of thermal crystalline transformation showed that the crystalline form L transformed into crystalline form A when heated to 100°C, and transformed into crystalline form C when heated to 190°C. NMR results showed that the structure of the compound was unchanged, and a dioxane solvent peak was observed at 3.57 ppm, with a crude estimated mass occupancy of about 0.6%. Water content test results showed that the water content of crystalline form L was 8.7%, which was consistent with the weight loss of TGA. In summary, crystalline form L was a dihydrate.

[0174] The peak positions of the XRPD diffraction peaks of crystalline form L are shown in the table below.

[0175] [Table 18]

[0176] Example 14 Preparation of Crystalline Form M of the Compound of Formula I 40 mg of the compound of formula I prepared in Example 1 was taken, ethylene glycol dimethyl ether was added until it was dissolved, chloroform was added dropwise until a solid was precipitated, and the mixture was stirred for 3-5 h, centrifuged, and the obtained solid was vacuum dried at room temperature overnight to obtain crystalline form M, which had poor crystallinity. The crystalline form M of the compound of formula I was characterized by XRPD, DSC, and TGA, as shown in Figures 25-26, respectively. The TGA results showed that the crystalline form M had a weight loss of 10.6% during heating to 200°C, and may decompose after 315°C. The DSC results showed that the crystalline form M had a heat-dissipating peak of crystalline transformation at around 228°C. The experimental results of thermal crystalline transformation showed that the crystalline form M was transformed into crystalline form C after heating to 260°C. According to the NMR results, the structure of the compound did not change, and a solvent peak of chloroform was observed at 8.32 ppm, and solvent peaks of 4-methyl-2-pentanone were observed at 0.85 ppm, 1.99 ppm, 2.06 ppm, and 2.30 ppm. Based on the integration results, the ratio of the compound to chloroform was calculated to be 1:0.2, and the ratio of the compound to 4-methyl-2-pentanone was calculated to be 1:0.2.

[0177] Example 15 Preparation of Crystal Form N of the Compound of Formula I 40 mg of the compound of formula I prepared in Example 1 was taken, ethylene glycol dimethyl ether was added until it was dissolved, acetonitrile was added dropwise until a solid was precipitated, and the mixture was stirred for 3-5 h, centrifuged, and the obtained solid was vacuum dried at room temperature overnight to obtain crystalline form N. The crystalline form N of the compound of formula I was characterized by XRPD, DSC, and TGA, as shown in Figures 27-28, respectively. The TGA results showed that the crystalline form N had a weight loss of 5.6% during heating to 150°C, and may decompose after 315°C. The DSC results showed that the crystalline form N had an endothermic signal around 100-160°C corresponding to the weight loss of TGA, and a crystalline transformation exothermic peak around 204°C. The experimental results of thermal crystalline transformation showed that the crystalline form N was transformed into crystalline form C with poor crystallinity after heating to 235°C. According to the NMR results, the structure of the compound did not change, and an acetonitrile solvent peak was observed at 2.07 ppm. The crude estimated mass fraction calculated from the integration results was about 5.0%, which was consistent with the weight loss in TGA. In summary, the crystalline form N is an acetonitrile solvate, and the ratio of the compound to acetonitrile was 1:0.6.

[0178] The peak positions of the XRPD diffraction peaks of crystalline form N are shown in the table below.

[0179] [Table 19]

[0180] Example 16 Preparation of Crystalline Form O of the Compound of Formula I 100 mg of the compound of formula I prepared in Example 1 was taken, 0.5 ml of N,N-dimethylformamide was added, and the mixture was heated until it was dissolved, and methanol was added dropwise until a solid was precipitated, and the mixture was cooled slowly to room temperature, stirred for 3-5 h, centrifuged, and the solid obtained was vacuum dried at room temperature overnight to obtain crystalline form O. The crystalline form O of the compound of formula I was characterized by XRPD, DSC, and TGA, as shown in Figures 29-30, respectively. The TGA results showed that the crystalline form O had a weight loss of 4.7% during heating to 110°C, a weight loss of 9.8% at 110-150°C, and may decompose after 315°C. The DSC results showed that the crystalline form O had endothermic signals at 80-110°C and 130-160°C corresponding to the weight loss of TGA. According to the NMR results, the structure of the compound was unchanged, and DMF solvent peaks were observed at 2.73 ppm, 2.89 ppm, and 7.95 ppm. The crude estimated mass occupancy was about 11.7% based on the integration results. In summary, the crystalline form O is a DMF solvate, and the ratio of the compound to DMF was 1:0.8.

[0181] The peak positions of the XRPD diffraction peaks of crystalline form O are shown in the table below.

[0182] [Table 20]

[0183] Example 17 Preparation of Crystalline Form P of the Compound of Formula I 100 mg of the compound of formula I prepared in Example 1 was taken, 1 ml of methanol was added, the mixture was heated to reflux, 1 ml of toluene was added dropwise, the mixture was cooled slowly to room temperature, stirred for 3-5 h, centrifuged, and the solid obtained was vacuum dried at room temperature overnight to obtain crystalline form P. The crystalline form P of the compound of formula I was characterized by XRPD, DSC and TGA, as shown in Figures 31-32, respectively. The TGA results showed that the crystalline form P had a weight loss of 8.0% during heating to 150°C, and may decompose after 315°C. The DSC results showed that the crystalline form P had one endothermic signal at 75-130°C, which corresponds to the weight loss of TGA. NMR results showed that the structure of the compound was unchanged, and toluene solvent peaks were observed at 2.30 ppm, 7.18 ppm, and 7.24 ppm, and methanol solvent peaks were observed at 3.17 ppm and 4.10 ppm. The crude mass occupancy of methanol was estimated to be about 1.7% based on the integration results. The water content test showed that the water content of crystalline form P was 8.2%, which was consistent with the weight loss of TGA. In summary, crystalline form P was a dihydrate.

[0184] The peak positions of the XRPD diffraction peaks of crystalline form P are shown in the table below.

[0185] [Table 21]

[0186] Example 18 Preparation of Crystalline Form Q of the Compound of Formula I 100 mg of crystalline form A of the compound of formula I was taken, 1 ml of tetrahydrofuran was added, stirred at room temperature for 3-5 h, centrifuged, and the solid obtained was vacuum dried at room temperature overnight to obtain crystalline form Q. The crystalline form Q of the compound of formula I was characterized by XRPD, DSC, and TGA, as shown in Figures 33-34, respectively. The TGA result showed that the crystalline form Q had a weight loss of 13.2% during heating to 200°C, and may decompose above 330°C. The DSC result showed that the crystalline form Q had an endothermic signal corresponding to the weight loss of TGA before 190°C. The NMR result showed that the structure of the compound did not change, and the solvent peaks of tetrahydrofuran were observed at 1.75 ppm and 3.59 ppm. The ratio of the compound to tetrahydrofuran was calculated from the integration result to be 1:0.6, and the crude estimated mass occupancy was about 8.4%. In summary, the crystalline form Q may be a tetrahydrofuran solvate containing water of crystallization.

[0187] Example 19 Preparation of Crystal Form R of the Compound of Formula I 100 mg of the compound of formula I prepared in Example 1 was taken, and dioxane was added until it was dissolved, and ethyl ether was added dropwise until a solid was precipitated, and the mixture was stirred for 3-5 h, centrifuged, and the obtained solid was vacuum dried at room temperature overnight to obtain crystalline form R. The crystalline form R of the compound of formula I was characterized by XRPD, DSC, and TGA, as shown in Figures 35-36, respectively. The TGA results showed that the crystalline form R had a weight loss of 15.6% during heating to 200°C, and may decompose after 315°C. The DSC results showed that the crystalline form R had an endothermic signal around 185°C, which corresponds to the weight loss of TGA. The experimental results of thermal crystal transformation showed that the crystalline form R was transformed into the crystalline form C after desolvation. According to the NMR results, the structure of the compound did not change, and a dioxane solvent peak was observed at 3.57 ppm, and ethyl ether solvent peaks were observed at 1.09 ppm and 3.38 ppm. From the integration results, the crude estimated mass occupancy was about 14.7%, the ratio of the compound to ethyl ether was 1:0.3, and the crude estimated mass occupancy was about 4.1%. In summary, the crystal form R was a dioxane solvate, and the ratio of the compound to dioxane was 1:0.9.

[0188] Example 20 Preparation of Crystalline Form S of the Compound of Formula I 100 mg of the compound of formula I prepared in Example 1 was taken, 0.5 ml of dimethyl sulfoxide was added, the mixture was heated until it dissolved, cooled to room temperature, ethanol was added dropwise until a solid precipitated, stirred for 3-5 h, centrifuged, and the solid obtained was vacuum dried at room temperature overnight to obtain crystalline form S. The crystalline form S of the compound of formula I was characterized by XRPD, DSC and TGA, as shown in Figures 37-38, respectively. The TGA result showed that the crystalline form S had a weight loss of 15.0% during heating to 230°C, and may decompose after 315°C. The DSC result showed that the crystalline form S had an endothermic signal around 190-230°C corresponding to the weight loss of TGA. The NMR result showed that the structure of the compound did not change, and a DMSO solvent peak was observed at 2.54 ppm. The crude estimated mass occupancy was calculated from the integration result to be about 14.2%, which was consistent with the weight loss of TGA. In summary, crystalline form S was a DMSO solvate, and the ratio of the compound to DMSO was 1:1.

[0189] The peak positions of the XRPD diffraction peaks of crystalline form S are shown in the table below.

[0190] [Table 22-1] [Table 22-2]

[0191] Example 21 Preparation of Crystalline Form T of the Compound of Formula I 100 mg of the compound of formula I prepared in Example 1 was taken, 4-methyl-2-pentanone was added until it dissolved, and the mixture was evaporated at room temperature until a solid precipitated. The solid was centrifuged and dried in vacuum at room temperature overnight to obtain crystalline form T. The crystalline form T of the compound of formula I was characterized by XRPD, DSC and TGA, as shown in Figures 39-40, respectively. The TGA results showed that the crystalline form T had a weight loss of 9.7% during heating to 130°C, a weight loss of 8.1% between 130 and 200°C, and decomposed after 315°C. The DSC results showed that the crystalline form T had an endothermic signal corresponding to the weight loss of TGA between 100 and 170°C. NMR results showed that the compound structure did not change, and 4-methyl-2-pentanone solvent peaks were observed at 0.85 ppm, 1.99 ppm, 2.06 ppm, and 2.30 ppm. The crude estimated mass fraction calculated from the integration results was 18.0%, which was consistent with the weight loss of TGA. In summary, crystalline form T is a solvate of 4-methyl-2-pentanone, and the ratio of the compound to 4-methyl-2-pentanone was 1:1.

[0192] The peak positions of the XRPD diffraction peaks of crystalline form T are shown in the table below.

[0193] [Table 23-1] [Table 23-2] [Table 23-3]

[0194] Example 22 Preparation of Crystalline Form U of the Compound of Formula I 100 mg of the compound of formula I prepared in Example 1 was taken, 1 ml of methanol was added, the mixture was heated to reflux, 1 ml of acetonitrile was added dropwise, the mixture was slowly cooled to room temperature, stirred for 3-5 h, centrifuged, and the solid obtained was vacuum dried at room temperature overnight to obtain crystalline form U. The crystalline form U of the compound of formula I was characterized by XRPD, DSC and TGA, as shown in Figures 41-42, respectively. The TGA results showed that the crystalline form U had a weight loss of 8.1% during heating to 200°C, and decomposed after 250°C. The DSC results showed that the crystalline form U had an endothermic signal corresponding to the weight loss of TGA at around 80-150°C, and had a heat dissipation signal of crystal transformation at 155-200°C. During the experiment, it was found that the crystalline form U transformed into the crystalline form L when left at room temperature for 3 days, and the experimental results of thermal crystal transformation showed that the crystalline form U transformed into the crystalline form C when heated to 250°C. According to the NMR results, the structure of the compound was unchanged, and the acetonitrile solvent peak was observed at 2.07 ppm. The crude estimated mass fraction was about 5.2% when calculated from the integration results. In summary, the crystalline form U is an acetonitrile solvate, and the ratio of the compound to acetonitrile was 1:1.

[0195] Example 23 Preparation of Crystalline Form V of the Compound of Formula I 100 mg of the compound of formula I prepared in Example 1 was taken, 1 ml of chloroform and 1 ml of ethanol were added, and the mixture was stirred at room temperature for 10-15 h, centrifuged, and the solid obtained was vacuum dried at room temperature overnight to obtain crystalline form V. The crystalline form V of the compound of formula I was characterized by XRPD, DSC, and TGA, as shown in Figures 43-44, respectively. The TGA results showed that the crystalline form V had a weight loss of 3.4% during heating to 200°C, and decomposed after 315°C. The DSC results showed that the crystalline form V had no obvious heat flow signal before 300°C. The experimental results of thermal crystal transformation showed that the crystalline form V was still crystalline form V when heated to 150°C, and the TGA results of the sample obtained by thermal crystal transformation showed that the crystalline form V had a weight loss of 1.6% during heating to 150°C. According to the NMR results, the structure of the compound did not change, and the chloroform solvent peak was observed at 8.32 ppm. From the integration results, the ratio of the compound to chloroform was calculated to be 1:0.1. In summary, the crystalline form V was anhydrous.

[0196] The peak positions of the XRPD diffraction peaks of crystalline form V are shown in the table below.

[0197] [Table 24-1] [Table 24-2]

[0198] Example 24 Preparation of Crystalline Form W of the Compound of Formula I 20 mg of the compound of formula I prepared in Example 1 was taken, and ethylene glycol monomethyl ether was added until it dissolved, and the mixture was put into ethyl ether for gas phase diffusion, and the solid obtained was dried overnight in vacuum at room temperature to obtain crystalline form W. The crystalline form W of the compound of formula I was characterized by XRPD, as shown in FIG. 45. According to the NMR results, the structure of the compound did not change, and the solvent peaks of ethyl ether were observed at 1.09 ppm and 3.38 ppm, and the solvent peaks of ethylene glycol monomethyl ether were observed at 3.24 ppm, 3.48 ppm, and 4.56 ppm. According to the calculation based on the integration results, the ratio of the compound to ethyl ether was 1:0.3, the crude estimated mass occupancy was about 3.7%, and the crude estimated mass occupancy was about 10.1%. In summary, the crystalline form W was a solvate of ethylene glycol monomethyl ether, and the ratio of the compound to ethylene glycol monomethyl ether was 1:0.7.

[0199] We found that the XRPDs of Form F, Form Q, Form R, Form S, Form U and Form W were very similar, and we speculated that these six forms were heteroisomorphic solvates.

[0200] Example 25 Preparation of Crystalline Form X of the Compound of Formula I 200 mg of crystalline form E of the compound of formula I was taken, and 1 ml of toluene was added, stirred at 50-60°C for 10-15 h, filtered, and the resulting solid was dried in vacuum at room temperature overnight to obtain crystalline form X. Crystal form X of the compound of formula I was characterized by XRPD, as shown in Figure 46.

[0201] Example 26 Preparation of Crystal Form Y of the Compound of Formula I 200 mg of crystalline form G of the compound of formula I was taken, and 1 ml of acetonitrile was added, stirred at 50-60°C for 10-15 h, filtered, and the resulting solid was dried in vacuum at room temperature overnight to obtain crystalline form Y. Crystal form Y of the compound of formula I was characterized by XRPD, as shown in Figure 47.

[0202] Example 27 Preparation of Crystalline Form Z of the Compound of Formula I 200 mg of the compound of formula I prepared in Example 1 was taken, 1 ml of water and 1 ml of N,N-dimethylformamide were added, and the mixture was stirred at room temperature for 10-15 h, filtered, and the solid obtained was dried under vacuum at room temperature overnight to obtain crystalline form Z. The crystalline form Z of the compound of formula I was characterized by XRD, DSC, and TGA, as shown in Figures 48-49, respectively. The TGA results showed that the crystalline form Z had a weight loss of 0.5% during heating to 100°C, a weight loss of 13.3% at 100-200°C, and decomposed after 330°C. The DSC results showed that the crystalline form Z had endothermic signals at 50-80°C and 110-180°C corresponding to the weight loss of TGA. NMR results showed that the compound's structure was unchanged, and DMF solvent peaks were observed at 2.73 ppm, 2.89 ppm, and 7.95 ppm. The crude mass fraction was estimated to be 14.0% based on the integration results, which was consistent with the weight loss from TGA. In summary, crystalline form Z is a solvate of DMF, and the ratio of the compound to DMF was about 1:0.9.

[0203] The peak positions of the XRPD diffraction peaks of crystalline form Z are shown in the table below.

[0204] [Table 25-1] [Table 25-2]

[0205] Thermal crystal conversion test Different crystal forms were used as raw materials, heated to the target temperature on a hot stage, kept at constant temperature for 1 minute, and cooled to room temperature to obtain solids, which were then subjected to XRPD testing. The results are shown in the table below.

[0206] Thermal crystal transformation results

[0207] [Table 26] The results showed that most of the crystalline forms were transformed into crystalline form C after heating, and crystalline form C was the more stable crystalline form at high temperatures, which is very useful for drug formulations, as the active ingredient is less likely to undergo crystalline form transformation due to heat during formulation, which would further affect its bioavailability and other parameters, and it was stable even when stored at temperatures higher than room temperature.

[0208] Dynamic moisture sorption / desorption analysis was performed using DVS Intrinsic (SMS, UK). The test was performed in gradient mode with a humidity change of 50%-95%-0%-50%, with a humidity change of 10% for each gradient within the range of 0% to 90%. The gradient endpoint was determined by the dm / dt method, and the gradient endpoint was determined when dm / dt was less than 0.002% for 10 minutes. After the test was completed, the samples were subjected to XRPD analysis to determine whether the solid morphology had changed.

[0209] The DVS results are shown in Figure 50. The DVS results show that form C had a weight gain of 0.20% at 95% humidity and a weight loss of 0.13% at 0% humidity, indicating that form C has little hygroscopicity, and the XRPD results show that the sample had no change in crystal form after the DVS test. As an anhydrous crystal form, form C does not absorb moisture and transform into a water-containing crystal form under high humidity conditions, which is very advantageous for the storage and formulation process of the drug.

[0210] stability studies

[0211] [Table 27]

[0212] Stability test 1 Approximately 20 mg of sample was weighed out and placed in a weighing bottle and placed under high temperature (60°C), high humidity (25°C, 92.5% RH), light exposure (25°C, 4500 Lux), and accelerated conditions (40°C, 75% RH), and samples were taken on the 7th and 15th days for XRPD characterization. The XRPD results in Figure 51 show that Form C was stable under high temperature, high humidity, light exposure, and accelerated conditions for 15 days, and no crystal form conversion occurred.

[0213] Stability test 2 For the crystalline form C sample, a double layered low density polyethylene bag was used as the inner packaging material, and a polyester / aluminum / polyethylene composite bag was used as the outer packaging material. The related substances were measured by HPLC at 0, 1, 2, 3 and 6 months under the conditions of 40°C±2°C and 75%RH±5%RH, respectively. The results are shown in the table below.

[0214] [Table 28] The results showed that crystalline form C had good stability within 6 months under the conditions of 40℃±2℃ and 75%RH±5%RH, and no obvious increase in related substances was observed.

[0215] Stability test 3 For the crystalline form C sample, a double layered low density polyethylene bag was used as the inner packaging material, and a polyester / aluminum / polyethylene composite bag was used as the outer packaging material. The related substances were measured by HPLC at 0, 3, 6, 9 and 12 months under the condition of 5℃±3℃, and the results are shown in the table below.

[0216] [Table 29] The results showed that, under the condition of 5℃±3℃, crystalline form C had good crystalline stability within 12 months, and no obvious increase of related substances was observed.

[0217] Stability test 4 For the crystalline form C sample, a double layered low density polyethylene bag was used as the inner packaging material, and a polyester / aluminum / polyethylene composite bag was used as the outer packaging material. The related substances were measured by HPLC at 0, 3, 6, 9 and 12 months under the conditions of 25°C±2°C and 60%RH±5%RH, respectively. The results are shown in the table below.

[0218] [Table 30] The results showed that crystalline form C had good stability within 12 months under the conditions of 25℃±2℃ and 60%RH±5%RH, and no obvious increase in related substances was observed.

[0219] Stability Test 5 For the crystalline form C sample, a double layered low density polyethylene bag was used as the inner packaging material, and a polyester / aluminum / polyethylene composite bag was used as the outer packaging material. The related substances were measured by HPLC at 0, 3, 6, 9 and 12 months under the conditions of 30℃±2℃ and 65%RH±5%RH, respectively. The results are shown in the table below.

[0220] [Table 31] The results showed that crystalline form C had good stability within 12 months under the conditions of 30℃±2℃ and 65%RH±5%RH, and no obvious increase in related substances was observed.

Claims

1. A crystalline polymorph of the compound of formula I, 【Chemistry 1】 where n is 0 to 2 and X is H. 2 A crystalline polymorph of the compound of formula I,

2. 2. The crystalline polymorph according to claim 1, wherein n is 2, the crystalline polymorph is crystalline form A, and the X-ray powder diffraction pattern employing Cu-Kα radiation has characteristic diffraction peaks at 2θ positions of 5.68°±0.2°, 11.44°±0.2°, 17.19°±0.2°, 24.94°±0.2°, 26.40°±0.2°, and 29.47°±0.2°.

3. The crystalline polymorph of claim 2, wherein the X-ray powder diffraction pattern further has characteristic diffraction peaks at 2θ positions of 12.68°±0.2°, 19.44°±0.2°, 19.79°±0.2°, and 23.27°±0.2°.

4. The crystalline polymorph of claim 2 or 3, whose X-ray powder diffraction pattern is essentially as shown in FIG.

5. 4. The crystalline polymorph of claim 2 or 3, wherein the crystalline form A has a DSC diagram and / or a TGA diagram of FIG.

6. 2. The crystalline polymorph according to claim 1, wherein n is 0, the crystalline polymorph is crystalline form C, and the X-ray powder diffraction pattern employing Cu-Kα radiation has characteristic diffraction peaks at 2θ positions of 11.03°±0.2°, 15.79°±0.2°, 16.97°±0.2°, 23.27°±0.2°, 23.76°±0.2°, and 27.61°±0.2°.

7. The crystalline polymorph of claim 6, wherein the X-ray powder diffraction pattern further has characteristic diffraction peaks at 2θ positions of 14.12°±0.2°, 19.73°±0.2°, 22.51°±0.2°, 25.37°±0.2°, 28.21°±0.2°, and 33.73°±0.2°.

8. The crystalline polymorph of claim 6 or 7, whose X-ray powder diffraction pattern is essentially as shown in FIG.

9. 8. The crystalline polymorph of claim 6 or 7, wherein the crystalline form C has a DSC diagram and / or a TGA diagram of FIG.

10. 2. The crystalline polymorph according to claim 1, wherein n is 2, the crystalline polymorph is crystalline form L, and the X-ray powder diffraction pattern employing Cu-Kα radiation has characteristic diffraction peaks at 2θ positions of 5.72°±0.2°, 11.49°±0.2°, 12.56°±0.2°, 14.33°±0.2°, 17.32°±0.2°, 25.33°±0.2°, 26.25°±0.2°, and 27.51°±0.2°.

11. The crystalline polymorph of claim 10, whose X-ray powder diffraction pattern is essentially as shown in Figure 23.

12. 11. The crystalline polymorph of claim 10, wherein the crystalline form L has the DSC and / or TGA diagram of FIG.

13. 2. The crystalline polymorph according to claim 1, wherein n is 2, the crystalline polymorph is crystalline form P, and the X-ray powder diffraction pattern employing Cu-Kα radiation has characteristic diffraction peaks at 2θ positions of 5.76°±0.2°, 11.55°±0.2°, 17.38°±0.2°, 23.12°±0.2°, 24.50°±0.2°, and 26.58°±0.2°.

14. The crystalline polymorph of claim 13, wherein the X-ray powder diffraction pattern further has characteristic diffraction peaks at 2θ positions of 14.60°±0.2°, 17.13°±0.2°, 25.91°±0.2°, and 29.51°±0.2°.

15. The crystalline polymorph of claim 13 or 14, whose X-ray powder diffraction pattern is essentially as shown in FIG.

16. 15. The crystalline polymorph of claim 13 or 14, wherein the crystalline form P has a DSC diagram and / or a TGA diagram of FIG.

32.

17. 2. The crystalline polymorph according to claim 1, wherein n is 0, the crystalline polymorph is crystalline form V, and the X-ray powder diffraction pattern employing Cu-Kα radiation has characteristic diffraction peaks at 2θ positions of 7.41°±0.2°, 11.05°±0.2°, 15.81°±0.2°, 16.97°±0.2°, 22.53°±0.2°, 23.29°±0.2°, and 27.63°±0.2°.

18. The crystalline polymorph of claim 17, wherein the X-ray powder diffraction pattern further has characteristic diffraction peaks at the 2θ positions of 14.16°±0.2°, 15.59°±0.2°, 19.73°±0.2°, 21.33°±0.2°, 23.78°±0.2°, 25.39°±0.2°, and 33.75°±0.2°.

19. The crystalline polymorph of claim 17 or 18, whose X-ray powder diffraction pattern is essentially as shown in Figure 43.

20. 19. The crystalline polymorph of claim 17 or 18, wherein the crystalline form V has a DSC diagram and / or a TGA diagram of Figure 44.

21. A pharmaceutical composition comprising a therapeutically effective amount of the crystalline polymorph of any one of claims 1 to 20, and a pharma- ceutically acceptable carrier and / or excipient.

22. Use of the crystalline polymorph of any one of claims 1 to 20 or the pharmaceutical composition of claim 21 in the manufacture of a medicament for treating primary hypercholesterolemia.